Pharmacological effects, formulations, and clinical research progress of curcumin - Hao, Minghui; Zhang, Chungang; Wang, Ti; Hu, Heng (Frontiers in Pharmacology, 2025)
Curcumin, a polyphenolic compound derived from the traditional Chinese medicine turmeric, which has a variety of pharmacological effects, including anti-cancer, anti-inflammatory, antioxidant, and antiviral properties. However, its clinical application is hindered by low solubility and bioavailability. To overcome these limitations, researchers have developed various formulations such as nanoformulations, solid dispersions, and microspheres. These advancements have led to improved therapeutic effects and have facilitated the progression of clinical research, primarily focusing on Phase I and Phase II trials for conditions like diabetes, obesity, and metabolic syndrome. In recent years, there has been a noticeable increase in Phase III and IV clinical trials, particularly concerning oral and dental diseases and arthritis. This article reviews recent literature from both domestic and international sources, providing a comprehensive overview of curcumin’s research progress, including its pharmacological mechanisms, formulation developments, and clinical studies.